Micronutrients and sarcopenia: current perspectives. Issue 3 (20th August 2021) - Robinson, Sian; Granic, Antoneta; Sayer, Avan Aihie
Abstract : Sarcopenia, a skeletal muscle disorder that is characterised by loss of muscle strength and mass, is common in older populations and associated with poorer health outcomes. Although the individual and economic costs of sarcopenia are widely recognised, current understanding of its pathophysiology is incomplete, limiting efforts to translate research evidence into effective preventive and treatment strategies. While nutrition is a key field of sarcopenia research, the role of differences in habitual diets, and the effectiveness of dietary change as a prevention or treatment strategy, is uncertain. There is a growing evidence base that links low micronutrient intakes to sarcopenia risk and/or its components (low muscle strength and mass, impaired physical performance), although there remain many gaps in understanding. There is some consistency in findings across studies highlighting potential roles for antioxidant nutrients, B vitamins and magnesium; however, the evidence is largely observational and from cross-sectional studies, often describing associations with different muscle outcomes. As low intakes of some micronutrients are common in older populations, there is a need for new research, particularly from well-characterised prospective cohorts, to improve the understanding of their role and importance in the aetiology of sarcopenia and to generate the evidence needed to inform dietary guidelines to promote muscle health.